Characterization of pectin extracted from muskmelon (Cucumis melo L.) - Nyarko, Benjamin; Agbenorhevi, Jacob K.; Wireko-Manu, Faustina D.; Kpodo, Fidelis M. (Journal of Science and Technology, 2024)
This is an article published in Journal of Ghana Science Association, Volume 20(1), 2021